2013
DOI: 10.1002/jbm.a.34492
|View full text |Cite
|
Sign up to set email alerts
|

Reduced toxicity and superior cellular response of preosteoblasts to Ti‐6Al‐7Nb alloy and comparison with Ti‐6Al‐4V

Abstract: There are serious concerns on the toxicity of vanadium in Ti-6Al-4V alloy. In this regard, we describe the biological footprint of Ti-6Al-4V and compare with a viable alternate Ti-6Al-7Nb alloy, in terms of novel experimentation pertaining to cellular activity that include qualitative and quantitative analysis of Feret's diameter of cells, area, and perimeter, and proteins-actin, vinculin, and fibronectin. Interestingly, Ti-6Al-7Nb was characterized by superior cell attachment, proliferation, viability, morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(50 citation statements)
references
References 30 publications
4
46
0
Order By: Relevance
“…One example of such a search is an attempt to replace commonly used in medicine Ti6Al4V alloy by Ti6Al7Nb alloy. The latter has better corrosion resistance and does not release toxic vanadium, and is also assigned to other positive traits …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One example of such a search is an attempt to replace commonly used in medicine Ti6Al4V alloy by Ti6Al7Nb alloy. The latter has better corrosion resistance and does not release toxic vanadium, and is also assigned to other positive traits …”
Section: Discussionmentioning
confidence: 99%
“…However, the proportions are reversed and non‐oxidized surface of the Ti6Al7Nb alloy allows a higher level of cell proliferation. Another article demonstrates a significantly higher proliferative potential of mouse preosteoblast MC3T3‐E1 subclone four grown on the surface of the Ti6Al7Nb alloy compared with the Ti6Al4V alloy, and a control culture. In turn, in the work no significant differences in the number of MG‐63 cell cultured on the polished mirror surface of Ti6Al4V and Ti6Al7Nb alloys were found, and authors concluded that “the composition of the alloy has no significant influence on cell interaction.” Another study demonstrates strong difference in proliferation of Saos‐2 cells depending on the surface roughness.…”
Section: Discussionmentioning
confidence: 99%
“…In general, no histological differences can be found with respect to bone healing in association with Ti and Ti-Al-V and both materials become osseointegrated [7]. However, concerns have been raised about the potential harmful effects of Al and V, particularly that the release of ions from the surface can induce adverse tissue reactions and immunological responses [5,[8][9][10]. It has also been claimed that these ions inhibit hydroxyapatite formation [11] and it has been suggested that they reduce the biomechanical anchorage of Ti-Al-V implants as compared to Ti [12,13].…”
Section: Introductionmentioning
confidence: 95%
“…3 In vitro experiments have shown that Ti-6Al-7Nb evoked similar cell responses to those of Ti, 4 and cell attachment, proliferation, viability, morphology, and spreading that were superior to Ti-6Al-4V. 5 In addition, the in vivo experiments showed that Ti-6Al-7Nb induced less inflammatory response than Ti-6Al-4V. 6 Considerable effort now goes into the modification of the surface of an implant to achieve stimulation and accelerate osseointegration.…”
Section: Introductionmentioning
confidence: 96%